The anti-hypercholesterolemic effect of low p53 expression protects vascular endothelial function in mice. - Francois Leblond; Steve Poirier; Carol Yu; Natacha Duquette; Gaetan Mayer; Eric Thorin (PLoS ONE, 2014)
To demonstrate that p53 modulates endothelial function and the stress response to a high-fat western diet (WD).Three-month old p53+/+ wild type (WT) and p53+/- male mice were fed a regular or WD for 3 months. Plasma levels of total cholesterol (TC) and LDL-cholesterol were significantly elevated (p<0.05) in WD-fed WT (from 2.1±0.2 mmol/L to 3.1±0.2, and from 0.64±0.09 mmol/L to 1.25±0.11, respectively) but not in p53+/- mice. The lack of cholesterol accumulation in WD-fed p53+/- mice was associated with high bile acid plasma concentrations (p53+/- =  4.7±0.9 vs. WT =  3.3±0.2 μmol/L, p<0.05) concomitant with an increased hepatic 7-alpha-hydroxylase mRNA expression. While the WD did not affect aortic endothelial relaxant function in p53+/- mice (WD =  83±5 and RD =  82±4% relaxation), it increased the maximal response to acetylcholine in WT mice (WD =  87±2 vs. RD =  62±5% relaxation, p<0.05) to levels of p53+/-. In WT mice, the rise in TC associated with higher (p<0.05) plasma levels of pro-inflammatory keratinocyte-derived chemokine, and an over-activation (p<0.05) of the relaxant non-nitric oxide/non-prostacyclin endothelial pathway. It is likely that in WT mice, activations of these pathways are adaptive and contributed to maintain endothelial function, while the WD neither promoted inflammation nor affected endothelial function in p53+/- mice.Our data demonstrate that low endogenous p53 expression prevents the rise in circulating levels of cholesterol when fed a WD. Consequently, the endothelial stress of hypercholesterolemia is absent in young p53+/- mice as evidenced by the absence of endothelial adaptive pathway over-activation to minimize stress-related damage.